Is Turkey a Favorable Environment for FDIs? - Demir, Memduh Alper (IGI Global, 2020)
The aim of this chapter is to measure the impact of institutional variables such as economic freedom and democracy on foreign direct investment from the European Union to Turkey. In this framework, the author models institutional factors affecting foreign direct investments. The model includes economic freedom index, political rights, civil liberties of Turkey, and Gross Domestic Products of selected European countries. In theoretical part, the perspective of institutional economics on economic freedoms and democracy is discussed. A brief literature about the relationship between foreign direct investments and economic freedoms and democracy is revealed. Stochastic frontier analysis was used in the implementation to show the relationship between variables and efficiency of European countries' foreign direct investments to Turkey. Proposals for policy implication have been made in the conclusion part. This chapter shows civil liberties and economic freedom index have positive effect on foreign direct investments that supports institutionalists.
Keywords: 9. Industry and infrastructure; 4. Education; 8. Economic growth; 1. No poverty; 16. Peace & justice